The Relationships between Thyroid Hormones and the Brain Serotonin (5-HT) System and Mood: Of Synergy and Significance in the Adult Brain- A Review (Faridpur Medical College Journal, 2015)
The use of thyroid hormones as an effective adjunct treatment for affective disorders has been studied over the past three decades and has been conformed repeatedly. Interaction of the thyroid and monoamine neurotransmitter systems has been suggested as a potential underline mechanism of action. While catecholamine and thyroid interrelationships have been reviewed in detail, the serotonin system has been relatively neglected. Thus, the goal of this article is to review the literature on the relationship between thyroid hormones and the brain serotonin (5-HT) system. In humans, neuroendocrine challenge studies in hypothyroid patients have shown a reduced 5-HT responsiveness that is reversible with replacement therapy. In the majority of the studies, the effects of thyroid hormone administration in animals will experimentally-induced hypothyroid sates include an increase in cortical 5-HT concentrations and a desensitization of auto inhibitory 5-HT1A receptors in the rap he area, resulting in disinhibition of cortical hippocampal 5-HT release. Furthermore, there is some indication that thyroid hormones may increase cortical 5-HT2 receptor sensitivity. In conclusion, there is robust evidence, particularly from animal studies, that the thyroid economy has a modulating impact in the brain serotonin system. Thus it is postulated that one mechanism, among others, through which exogenous thyroid hormones may exert their modulatory effects in affective illness is via an increase in serotonergic neurotransmission, specifically by reducing the sensitivity of 5- HT1A auto receptors in the raphe area, and by increasing 5--HT2 receptor sensitivity.Faridpur Med. Coll. J. 2014;9(2): 98-101